2019
DOI: 10.3390/ma12020241
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Nanoporous Activated Carbon Derived from Prawn Shell and Its Application for Removal of Heavy Metal Ions

Abstract: The aim of this study was to optimize the adsorption performance of activated carbon (AC), derived from the shell of Penaeus vannamei prawns, on heavy metal ions. Inexpensive, non-toxic, and renewable prawn shells were subjected to carbonization and, subsequently, KOH-activation to produce nanoporous K-Ac. Carbonized prawn shells (CPS) and nanoporous KOH-activated carbon (K-Ac) from prawn shells were prepared and characterized by FTIR, XRD, BET, SEM, and TEM. The results showed that as-produced K-Ac samples we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(27 citation statements)
references
References 65 publications
2
25
0
Order By: Relevance
“…In this figure, it can be seen that the Pb 2+ adsorption was rapid in the first stage of adsorption, then slowly increased with time, becoming almost constant after 120 min. This phenomenon can be attributed to the high availability of vacant adsorption sites in the first stage of adsorption, followed by an increase in repulsive forces due to the presence of the adsorbed ions, making the remaining sites more difficult to access [37,41]. It was observed that the ion removal percentage was slightly reduced with an increase in initial concentration (Figure 4 and Figure 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this figure, it can be seen that the Pb 2+ adsorption was rapid in the first stage of adsorption, then slowly increased with time, becoming almost constant after 120 min. This phenomenon can be attributed to the high availability of vacant adsorption sites in the first stage of adsorption, followed by an increase in repulsive forces due to the presence of the adsorbed ions, making the remaining sites more difficult to access [37,41]. It was observed that the ion removal percentage was slightly reduced with an increase in initial concentration (Figure 4 and Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Pseudo-first-order Equation (3) assumes that the adsorption rate is based on the adsorption capacity. The pseudo-second-order model, Equation (4), is based on the assumption that the adsorption is controlled by the chemisorption mechanism, involving valency forces through electron sharing or transfer between the adsorbent and adsorbate [36,37]. log(qeqt)=logfalse(qefalse)k1t2.303 tqt=1k2qe2+tqe where q t and q e (mg/g) are the amount of Pb 2+ adsorbed per mass of adsorbent (g) at time t (min) and at equilibrium, respectively, and k 1 (1/min) and k 2 (mg/(g∙min)) are the rate constants of the pseudo-first-order and pseudo-second-order models, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The PFO model (Equation (11)) assumes the adsorption rate based on the adsorption capacity. The PSO (Equation (12)) model is based on the assumption that the adsorption is controlled by the chemisorption mechanism, involving valency forces through electron sharing or transfer between the adsorbent and the adsorbate [38,40]. For the intra-particle diffusion model (Equation (14)), the plot of q t versus t 0.5 is assumed to be linear, passing through the origin; otherwise, some other mechanism may be involved.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, investigations are ongoing for preparation of charcoal using low cost materials, natural materials, agricultural waste, etc. 10 . Regarding adsorption process, it is performed by batch, up-flow or down-flow continuous fixed bed, continuous fluidized bed, continuous moving bed and oscillated (pulsed) bed, in which batch and up-flow continuous fixed bed adsorption investigations are more feasible due to easy and cheap technique and can removed most of contaminations 11 .…”
mentioning
confidence: 99%